Methyl 5-bromo-2-hydroxybenzoate - Mustafa, Ghulam (International Union of Crystallography, 2012)
The title compound, C(8)H(7)BrO(3), is almost planar (r.m.s. deviation for the non-H atoms = 0.055 Å). In the crystal, O—H⋯O hydrogen bonds link the molecules into C(6) chains propagating in [010]. Very weak aromatic π–π interactions [centroid–centroid distances = 3.984 (5) and 3.982 (5) Å] also occur.